Samouel Beji, Le développement financier pour les pays du sud de la Méditerranée à l’épreuve de la mondialisation financière - Samouel Beji (Revue de la Régulation)
The central theme of the thesis is the financial development issue in a context of financial globalization for the south Mediterranean Sea countries. The choice of this theme is motivated by the importance of the economic development and the growth in these countries, which are usually the subject of political instabilities and are distinguished by weak political institutions. The aim in this thesis is to point out that the financial openness in the conditions of the south Mediterranean Sea countries would be detrimental to its financial development. By contrast, the financial openness would be beneficial to the financial development, in the presence of the adequate legal and institutional development. The model used links financial development indicators to institutional and legal indicators, in order to calculate institutional thresholds. Further, on the one hand, we check the nature of the relationship existing between institutional development, banking regulation and banking development. On the other hand, we test the relationship that exists between banking development and economic growth. To claim so, we used the GMM (General Method of Moments) system on dynamic panel data for nineteen countries of the MENA region, between 1980 and 2005, in the 2 estimations.